FINANCIAL RATIOS AND ENERGY STOCK PERFORMANCE: A STUDY ON INDONESIA’S ENERGY SECTOR (2019-2023) - Tampubolon, Manuel Vivien Ricardo; Nirawati, Lia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
The volatility of the energy sector’s price necessitates a thorough assessment of financial performance indicators to guide investment decisions. This study investigates the impact of Dividend Yield, Earnings Per Share (EPS), Price Earnings Ratio (PER), and Net Profit Margin (NPM) on stock prices of energy companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. This research uses multiple linear regression analysis; the results indicate that all variables significantly influence stock prices simultaneously and partially. Dividend Yield reflects potential cash returns in dividend form, enhancing investor expectations. Earnings Per Share demonstrates the company’s ability to generate profits, while Net Profit Margin highlights operational efficiency, strengthening market confidence. The price earnings ratio serves as an indicator of the market’s perception of future growth prospects. The F-test confirms that these variables collectively shape stock price dynamics. These findings align with previous studies, emphasizing the crucial role of fundamental financial metrics in stock valuation and investment analysis.